Evaluation of workability and mechanical properties of asphalt binder and mixture modified with waste toner. (22nd March 2021) - Huang, Jiandong; Kumar, G. Shiva; Sun, Yuantian
Highlights: Incorporating the waste toner in asphalt mixtures. Workability properties evaluated using densification indices and viscosity test. Rutting properties evaluated using wheel tracking device and MSCR test. Moisture induced damage properties evaluated using ITS and BBS test. Abstract: In recent years, disposal of bulk quantity of waste toner generated from the manufacturing process, copying machines, and laser printers has been a huge problem. In this study, an attempt has been made to overcome these problems by incorporating the waste toner in asphalt mixtures in a proper proportion. This study aims to evaluate the effect of varying dosages (4%, 8%, 12%, and 16%) of waste toner on workability and mechanical properties (rutting and moisture-induced damage) of asphalt mixtures. Workability properties were evaluated using densification indices (Locking point method) and viscosity test. Rutting properties were evaluated using the wheel tracking device and multiple stress creep recovery tests. Moisture-induced damage properties were evaluated using indirect tensile strength (Modified Lottman) and bitumen bond strength test. Results show that the addition of waste toner makes asphalt binder stiffer, reduces moisture susceptibility, and pumping ability. Furthermore, the addition of waste toner reduces workability and resistance to moisture-induced damage properties but increases resistance to rutting properties of asphalt mixtures irrespective of dosage rate.